Fixed bed adsorption and breakthrough modelling of activated porous carbon derived from compost for post-combustion CO2 capture - Karimi, Mohsen (2019)
In the recent years, synthesis, preparation and development of valuable carbon materials have received much interest in the view of energy efficiency and sustainability for various applications in CO2 capture, wastewater treatment and gas storage studies. On the other hand, based on European legislation to management of solid wastes and limiting the utilization of fertilizers from waste as well as finding approaches to manage these materials, novel approaches are required [3]. In this study, the obtained compost by mechanical biological treatment plant from municipal solid waste has been considered as a source of adsorbents for CO2 capture.